Models of partnership within family‐centred care in the acute paediatric setting: a discussion paper. (11th November 2016) - Dennis, Christine; Baxter, Pamela; Ploeg, Jenny; Blatz, Susan
Abstract: Aims: A discussion of partnership in the context of family‐centred care in the acute paediatric setting, through a critical analysis of partnership models. Background: Paediatric healthcare practitioners understand the importance of family‐centred care, but struggle with how to translate the core tenets into action and are confused by several rival terms. Partnering relationships are included in definitions of family‐centred care, yet less is known about strategies to fully engage or support parents in these partnerships. A rigorous examination of concepts embedded in family‐centred care such as partnership may provide a better understanding of how to implement the broader concept and support exemplary care in today's clinical practice environment. Design: Discussion paper. Data sources: Electronic search (January 2000 ‐ December 2014) performed on CINAHL, Medline, EMBASE, Sociological Abstracts and PsychINFO using keywords partnership, family‐centred care and conceptual framework . Eligible references were drawn from the databases, reference lists and expert sources. Eight models met inclusion criteria and had currency and relevance to the acute paediatric setting. Implications for nursing: Nurses should continue exploring partnership in various paediatric contexts given the wide‐ranging definitions, lack of operational indicators and need for stronger relational statements in current models. An examination of key strategies, barriers and facilitators of partnership is recommended. Conclusion: One partnership model had both high overall maturity and best fit with family‐centred care principles. All models originate from Western and developed countries, indicating that future partnership models should be more geographically, culturally and economically diverse.